Anatomy of the Perla Flavescens - Blachly, John Howard (My University, 1900)
Introduction: This little insect is classified differently by authors. Sedgwick in Cambridge Natural History, Vol. V places it in the order Neuroptera. Suborder Pseudo Neuroptera, families Embiidae Thermitidae, Psocidae, and Perlidae. Miall places it between the Sialidae and Epimeridae. His classification of families is as follows: Trichoptera, Sialidae, Perlidae, Ephemeridae, Odonata, Rhynchota, and Podura. Comstock places it in an order by itself, Plecptera, family Perlidae, and just above Odonata. It is an insect little worked out. Sedgwick says that there are but twenty-four species in Great Britain, and not over two hundred species named in all the collections of the world. But as the Perla is very widely distributed, it is likely that the number exceeds two or three thousand species. Fossils of the Perlidae have been found in rocks of the carboniferous strata of Commentry, as well as embedded in amber. In its life history, it has two distinct and abrupt stages. The longer one, or larva stage, is entirely aquatic, and the second, short, image stage is aerial. The larva requires a year for its growth, breathes with gills, and swims freely by means of its legs which are well provided with swimming hairs. It is carniverous, living on its near relatives, the Epimeridae. Swift flowing, foamy streams, such as mountain torrents, are its natural homes. Here they may be found in great abundance in the spring and summer, living under rocks the size of one's hand and larger. On lifting such a rock out of the water, and examining its under surface, you will see them clinging to it, or crawling to the darkest recesses. Both the Perlidae and Epimeridae will be found there.
Citation: Blachly, John Howard. Anatomy of the Perla Flavescens. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Entomology; Neuroptera; Perla Flavescens; Epimeridae; Perlidae; Theses